2015
DOI: 10.1186/s12917-015-0565-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma lipidome profile of dairy cows during the transition period

Abstract: BackgroundThe transition period of dairy cows, around parturition and the onset of lactation, involves endocrine and metabolic changes to compensate for an increased energy requirement aggravated by reduced feed intake. Transition cows adjust to the resulting negative energy balance with the mobilization of lipids from the adipose tissues yielding increased blood levels of non-esterified fatty acids and ketone bodies like β-hydroxybutyrate.ResultsTo study the biochemical adaptations underlying this physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 30 publications
6
40
0
2
Order By: Relevance
“…In contrast, a decrease in serum triglycerides and VLDL values was found at calving and postpartum time points compared to prepartum time points. The changes found in these parameters agree with the results of previous studies (Imhasly et al, 2015;Van den Top et al, 2005;Kessler et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, a decrease in serum triglycerides and VLDL values was found at calving and postpartum time points compared to prepartum time points. The changes found in these parameters agree with the results of previous studies (Imhasly et al, 2015;Van den Top et al, 2005;Kessler et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…The temporary drop in phospholipids levels on the day of parturition may be due to an increase in phospholipase activity in order to gain energy (Jacobs et al, 2013). In addition to insufficient hepatic VLDL secretion, the decrease in triglyceride levels and concomitant rise in phospholipids after parturition may be due to an increase in mammary lipoprotein lipase activity (Van den Top et al, 2005) in order to satisfy the energy requirements and the fat mammary gland transfer for milk yield (Fiore et al, 2014;Imhasly et al, 2015). Serum Total-Chol and LDL values showed a decrease from the prepartum to the postpartum period, whereas HDLs showed lower values 15 and 30 days after calving with respect to prepartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common feature of these phospholipids is their requirement for the secretion of hepatic TAG as very low-density lipoprotein particles. Thus, an increased formation and secretion of these phospholipids after birth has been regarded as a means of the liver to prevent accumulation of lipids [88]. In the present study, we observed that concentrations of all the individual phospholipids, and even their molecular species, in plasma of dairy cows in week 1 postpartum are not influenced by feeding GSGME.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, it has been observed that hepatic metabolism of glycerol- and ether phospholipids is closely linked to plasma concentrations of NEFA, BHBA and glucose, three key factors of the metabolic status of dairy cows during early lactation [20]. Imhashly et al [88] recently showed, using lipidomic analysis of plasma, that concentrations of some unsaturated PC, LPC and SM species (such as PC 36:4, PC 36:5, PC 36:6, LPC 18:1, LPC 18:2, LPC 18:3, SM 39:1, SM 43:3) in dairy cows are continuously increasing after birth. A common feature of these phospholipids is their requirement for the secretion of hepatic TAG as very low-density lipoprotein particles.…”
Section: Discussionmentioning
confidence: 99%